The Neuropsychiatric Approach to the Assessment of Patients in Neurology - Trapp, Nicholas T.; Martyna, Michael R.; Siddiqi, Shan H.; Bajestan, Sepideh N. (Seminars in Neurology, 2022)
Neuropsychiatry is a clinical neuroscience specialty focused on the evaluation and treatment of patients who present with symptoms at the intersection of neurology and psychiatry. Neuropsychiatrists assess and manage the cognitive, affective, behavioral, and perceptual manifestations of disorders of the central nervous system. Although fellowship training in behavioral neurology-neuropsychiatry exists in the United States and several other countries internationally, the need for neuropsychiatric expertise greatly outweighs the number of specialists in practice or training. This article serves as a primer for both neurologists and psychiatrists seeking to improve or refresh their knowledge of the neuropsychiatric assessment, including detailing aspects of the history-taking, physical exam, psychometric testing, and associated diagnostic work-up. In doing so, we urge the next generation of neurologists and psychiatrists to take on both the opportunity and challenge to work at the intersection of both clinical neuroscience specialties using an integrated neuropsychiatric perspective.
Keywords: neuropsychiatry; assessment; behavioral neurology; interview; education